Experimental studies on combustion and emissions of RCCI (reactivity controlled compression ignition) with gasoline/n-heptane and ethanol/n-heptane as fuels. (August 2015) - Qian, Yong; Wang, Xiaole; Zhu, Lifeng; Lu, Xingcai
Abstract: This paper presents an experimental study on the combustion and emissions characteristics of RCCI (reactivity controlled compression ignition) combustion in which in-cylinder direct injection of n-heptane combined with port injection of ethanol and gasoline, respectively, are used with a single-cylinder engine. Results show that, when the system is fueled with ethanol/n-heptane at a specific overall lower heating value per-cycle, the ignition delay of RCCI combustion increases greatly but the in-cylinder temperature and pressure drop severely for a larger premixed ratio. NOx and soot emissions are significantly improved for RCCI combustion under conditions of increased premixed ratio. At different premixed ratios, the HC (hydrocarbon) emission of gasoline/n-heptane is lower than that of ethanol/n-heptane, but the NOx and soot emissions are higher than those obtained with ethanol/n-heptane. When the premixed ratio is approximately 0.57, the indicated thermal efficiencies of both gasoline/n-heptane and ethanol/n-heptane reach their maximum values. When fueled with ethanol/n-heptane along with the increase in engine load, CO, NOx and soot emissions are lower than fueled with gasoline/n-heptane, but the HC emissions are higher. When IMEP (indicated mean effective pressure) is higher than 6 bar, the indicated thermal efficiency of ethanol/n-heptane is higher than that of gasoline/n-heptane. Ethanol is a good candidate to replace gasoline as port injected fuel in RCCI mode at heavy loads. Highlights: RCCI combustion with ethanol/n-heptane and gasoline/n-heptane as fuels was studied. Latent heat value and cetane number of PI fuels have strong impacts on combustion. NOx emissions of ethanol/n-heptane RCCI combustion were greatly decreased. Port injected ethanol has a highly beneficial effect on the soot emissions.